Desmoplastic Trichoepithelioma: An Infrequent Entity not to be Missed: Report of Two Cases. Issue 5 (8th June 2015) - Nuno‐Gonzalez, Almudena; Colmenero, Isabel; de Prada, Inmaculada; Noguera‐Morel, Lucero; Martorell‐Calatayud, Antonio; Hernandez‐Martin, Angela; Torrelo, Antonio
Abstract Desmoplastic trichoepitheliomas are rare benign tumors with follicular differentiation. They have rarely been described in children. We report two children with this uncommon condition.